Can Diffuse Idiopathic Skeletal Hyperostosis Be Diagnosed by Plain Lumbar Spine X-Ray Findings Alone?. Issue 2 (March 2022) - Misaki, Hiroshi; Morino, Tadao; Hino, Masayuki; Murakami, Yusuke; Imai, Hiroshi; Miura, Hiromasa
Study Design: Retrospective case-control study Objectives: To determine whether diffuse idiopathic skeletal hyperostosis (DISH) can be diagnosed based on anterior longitudinal ligamental ossification in the lumbar spine using plain lumbar spine X-ray images. Methods: This study included 100 patients (59 men and 41 women; mean age, 64.8 ± 13.8 years; range, 27-89 years) who underwent computed tomography (CT) of the chest to the pelvis in our hospital and plain lumbar spine radiography within 6 months before and after CT scanning. DISH was diagnosed based on the thoracolumbar spine CT findings using Resnick's diagnostic criteria. The patients were grouped according to DISH diagnosis into the DISH (+) and DISH (−) groups. On the frontal and lateral lumbar spine X-ray images, each spinal level from Th11/12 to L5/S was scored based on the Mata scoring system. The distribution of the Mata scores was compared between the 2 groups. Results: Forty (40%) patients were diagnosed with DISH based on the CT findings. A cutoff value ≥8 provided a sensitivity of 75% and specificity of 100% for diagnosing DISH, thus, indicating the validity of the cutoff value. In the DISH (−) group, no patient had ≥3 consecutive spinal levels with a Mata score ≥2, suggesting that DISH can be diagnosed on the basis of at least 3 consecutive spinal levels with a Mata score ≥2. Conclusion: On lumbar spine X-ray images of the T11/12 to L5/S levels, a Mata score ≥2 for at least 3 consecutive levels or a total score ≥8 strongly indicates the presence of DISH.